Analysis of Difficulties Encountered by MSMEs in Fulfilling Tax - Prastiwi, Putri Intan; Nugroho, Novemy Triyandari; Ali, Nur Aishah Mohd; Juniasari, Rosita (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This study aims to analyze the obstacles faced by Micro, Small, and Medium Enterprises (MSMEs) in fulfilling tax obligations in Surakarta City. The research method employs a qualitative approach with a snowball sampling technique to determine informants from MSME actors. Data were collected in-depth interviews, and documentation, then analyzed descriptively and thematically. The results indicate that MSME tax compliance remains low, with four main obstacles identified: (1) low literacy in taxation and accounting, (2) limited access and digital skills in using electronic tax services, (3) negative perceptions of tax as an additional business burden, and (4) lack of socialization and assistance from tax authorities. These findings are consistent with international studies emphasizing the importance of literacy, trust, fairness, as well as institutional and technological support in influencing MSME tax compliance. The study recommends enhancing tax education, providing intensive assistance, strengthening digital infrastructure, and fostering perceptions of a fairer and more transparent tax system to improve tax compliance in the MSME sector.